Fifty Years of Sporadic Coral Reef Calcification Estimates at One Tree Island, Great Barrier Reef: Is it Enough to Imply Long Term Trends? - Davis, Kay L.; McMahon, Ashly; Kelaher, Brendan; Shaw, Emily; Santos, Isaac R (Frontiers in Marine Science, 2019)
Estimates of coral reef ecosystem calcification (Gnet) and productivity (Pnet) provide insight into coral community health and functionality in response to short- and long-term stressors such as ocean warming and acidification. Here, we investigate spatial variability in calcification and organic production at One Tree Island (OTI) and compare our new observations to sporadic metabolic rates reported over the previous 50 years on the same reef flat. Gnet and Pnet estimates at the nearshore site were 50% and 166% lower than an offshore site with a shift in organic production from net productive to net respiratory. Contrary to expectations, calcification rates in 2017 (145.7 ± 20.24 mmol m-2 d-1) were comparable to the 1970’s estimate (125.0 ± 12.5 mmol m-2 d-1) and 400% greater than similar observations in 2014. Our results indicate only weak associations between Gnet and aragonite (Ωar). A local increase in coral cover from 18% in 2014 to 31% in 2017 was the likely driver of increased calcification. A steeper TA – DIC slope in 2017 demonstrates a greater control of calcification on seawater carbonate chemistry than prior years. Overall, these results highlight the importance of site selection and replication when comparing metabolic datasets, and demonstrate major short-term variability in metabolic rates. The predictive capabilities of ecosystem metabolism studies may be constrained by using the available short-term datasets to represent long-term calcification trends.